The Effect of Internal Audit on The Quality of Financial Reporting: The Mediating Roles of Internal Control and Management Accountability in Private Hospitals in Lumajang Regency, Indonesia - Jumkhairiyah Jumkhairiyah; Agung Budi Sulistyo; Ahmad Roziq (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the effect of Internal Audit on Financial Reporting Quality, both directly and indirectly through the mediating roles of Internal Control and Management Accountability, in private hospitals in Lumajang Regency, Indonesia, that have implemented the Hospital Management Information System (SIMRS). An explanatory quantitative design was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Primary data were collected through questionnaires from 55 respondents selected using purposive sampling from six private hospitals, including finance staff, Internal Supervisory Unit (SPI) members, and management personnel. The findings reveal that Internal Audit has no significant direct effect on either Financial Reporting Quality or Internal Control. Conversely, Internal Audit significantly enhances Management Accountability, while both Internal Control and Management Accountability positively influence Financial Reporting Quality. Mediation analysis indicates that Internal Control does not mediate the relationship between Internal Audit and Financial Reporting Quality, whereas Management Accountability fully mediates this relationship. The study extends Agency Theory by demonstrating that the effectiveness of Internal Audit in improving financial reporting quality depends primarily on strengthening managerial accountability rather than solely on reinforcing internal control mechanisms, providing practical implications for governance improvement in private hospitals implementing SIMRS.